Storage and release of spermatozoa from the pre-uterine tube reservoir - Freeman, S.L.; England, Gary C.W. (Public Library of Science, 2013)
In mammals, after coitus a small number of spermatozoa enter the uterine tube and following attachment to uterine tube epithelium are arrested in a non-capacitated state until peri-ovulatory signalling induces their detachment. Whilst awaiting release low numbers of spermatozoa continually detach from the epithelium and the uterine tube reservoir risks depletion. There is evidence of attachment of spermatozoa to uterine epithelium in several species which might form a potential pre-uterine tube reservoir. In this study we demonstrate that: (1) dog spermatozoa attach to uterine epithelium and maintain flagellar activity, (2) in non-capacitating conditions spermatozoa progressively detach with a variety of motility characteristics, (3) attachment is not influenced by epithelial changes occurring around ovulation, (4) attachment to uterine epithelium slows capacitation, (5) capacitated spermatozoa have reduced ability to attach to uterine epithelium, (6) under capacitating conditions increased numbers of spermatozoa detach and exhibit transitional and hyperactive motility which differ to those seen in non-capacitating conditions, (7) detachment of spermatozoa and motility changes can be induced by post-ovulation but not pre-ovulation uterine tube flush fluid and by components of follicular fluid and solubilised zona pellucida, (8) prolonged culture does not change the nature of the progressive detachment seen in non-capacitating conditions nor the potential for increased detachment in capacitating conditions. We postulate that in some species binding of spermatozoa to uterine epithelium is an important component of the transport of spermatozoa. Before ovulation low numbers of spermatozoa continually detach, including those which are non-capacitated with fast forward progressive motility allowing the re-population of the uterine tube, whilst around the time of ovulation, signalling from as-yet unknown factors associated with follicular fluid, oocytes and uterine tube secretion promotes the detachment of large numbers of capacitated spermatozoa with hyperactive motility that may contribute to the fertilising pool.